Vocationalisation of secondary education revisited - Lauglo, Jon [Herausgeber]; Maclean, Rupert [Herausgeber] (Springer-Verlag, 2005)
"The book is a cutting-edge contribution to the debate which has occured for some time on the pros and cons of secondary education becoming more closely and explicitly related to preparing young people for the world of work. The book provides concrete examples of the vocationalisation of secondary education, with particular reference to the situation in Africa." Vocationalised secondary education "is here understood as being a curriculum which remains overwhelmingly 'general' or academic in nature, but which also includes vocational or practical subjects as a minor portion of the timetable during the secondary school course." (Publisher, BIBB-Doku)
Keywords: S 1.1 Allgemeinbildende Schule; S 1.2 Berufsvorbereitung; I 2.3.4 Asien; I 2.3.1 Afrika; I 2.3.3 Lateinamerika; Allgemeinbildendes Schulwesen; Sekundarbereich; Berufsvorbereitung; Berufsbildung; Asien; Afrika; USA